Hubungan Tingkat Pengetahuan Mengenai Hubungan Seksual Pada Ibu Hamil Primigravida Terhadap Kecemasan Pada Trimester I Di Puskesmas Kartasura, Sukoharjo - Syndie, Diara Puspita; , Arina Maliya, S. Kep. MSi. Med; , Okti Sri Purwanti, S.Kep., M.Kep., Ns., Sp.Kep. M.B (2016)
Background : Pregnancy is a natural proces experienced by women and becomean important event in life them. Every women a pregnancy in this own thought about pregnant women because they have never experienced. The kind of thinkingaffect how it respond to pregnancy. Some women think og pregnancy as a disease, ugliness,or embarrasing as unattartive body shape as before pregnancy, even they thought ould interfereeith their sexual relationship with their husband. Objective: The purpose the study was to determine the relationship of the sexual relationship in the primigravida pregnant women to anxiety in the first trimester in Puskesmas Kartasura, Sukoharjo. Methods of study : The research is a quantitative study using a cross sectional design. The population in this study a total of 32 people with a total sampling technique. Analysis tools used by Chi- Square (2). Conclusions : 1) The level of knowledge abaout the sexual relationship in pregnant women primigravidae majority have sufficient knowledge level as many as 17responden; 2)Anxiey level respondent most are clessified as mild anxiety as much as 17 respondent; 3) There is significant relationship between the level of knowledge about the sexual relationship to anxiety primigravidae pregnant women in the first trimester in Puskesmas Kartasura, Sukoharjo.